Pengaruh Capital Expenditure terhadap Cash Holding dengan Tata Kelola Perusahaan sebagai Variabel Moderasi pada Perusahaan Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2021–2024 - Kezia Adiel Vania; Maryono Maryono (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Cash holding is a crucial aspect of maintaining corporate liquidity, particularly when companies manage commercial operations and long-term investment needs. Capital expenditure is expected to influence cash holding levels, while corporate governance is anticipated to play a role in strengthening or weakening this relationship. This study aims to analyze the effect of capital expenditure on cash holding, with corporate governance serving as a moderating variable, focusing on food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The study employs a quantitative approach using secondary data obtained from annual financial reports. The sample was selected using purposive sampling, resulting in 136 observations after the elimination of outliers. Data analysis was conducted using Moderated Regression Analysis (MRA) with the aid of IBM SPSS Statistics 31. The results indicate that capital expenditure does not have a significant effect on cash holding. Furthermore, corporate governance does not moderate the impact of capital expenditure on cash holding. These findings suggest that cash holding policies in food and beverage companies are influenced more by factors other than capital expenditure and the corporate governance mechanisms examined in this study.